Evaluation Of Graha Nusantara’s Operational Risk Management Process Using ISO 31000:2018 - Savira Rima Aulia (UNIVED Press, 2024)
Graha Nusantara is one of the business units of cooperative x which is engaged in building rental. Since the pandemic in 2020, Graha Nusantara has experienced a decrease in demand for building rentals which has led to a decrease in revenue. In addition, Graha Nusantara has also experienced problems related to its business operations such as canceling events by consumers for various reasons, building maintenance and management, employee management to those related to vendor partners. This causes Graha Nusantara to continue to lose money due to ineffective building operations which can actually be prevented by streamlining Graha Nusantara's operations. This study aims to evaluate operational risk management in the Graha Nusantara business unit, which is a building leasing business, with reference to risk management standards based on ISO 31000. The method used in this research is descriptive qualitative analysis with a case study approach, through interview and documentation data collection techniques. The results showed that risk management has not determined the scope, context and criteria process according to ISO 31000 and nineteen risks with various levels of risk were identified. Therefore, this study recommends handling each risk and it is expected that management establishes a risk management policy, especially operational risk